Representations of Kurdish national identity in the traditional story of Mem and Zin The dream of the state and the challenges of formation - Alwan, Prof.Dr. Ibtisam Hatem; Alwan, Prof.Dr. Khalida Hatem (Sulaimani Journal for Humanities, 2025)
The content of this research is directed to the role of Kurdish literature - specifically novels - in establishing the formation of the great state of Kurdistan, identifying the factors of achievement and the reasons for failure, and focusing on the history of the Kurdish people and pride in it as a history that confirms the civilizational depth of that people. The selection of the epic (Mam and Zin) comes as the ideal model for understanding the national and cultural identity of the Kurdish people and its specificity. Therefore, the study will be divided into four sections - based on the trinity of national identity - represented by three sections, and its challenges represented by one section, in addition to the introduction that deals with the Kurdish novel in its historical context. The first section will deal with the geography of narration equivalent to the element of land, while the second section will deal with the imagined Kurdish nation group with what it includes of the specificity of the group with its culture, customs, traditions and language equivalent to the element of the people/individuals, while the third section deals with the narratives of the Kurdish nation equivalent to history, while the fourth section will deal with the challenges facing the Kurdish national identity represented by the political conflict and internal disputes according to what is presented the fictional imagination
Keywords: Kurdish national identity; imagined communities of the Kurdish nation; narratives of the Kurdish nation